1955
DOI: 10.1161/01.cir.12.4.557
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cardiac Output with Age

Abstract: In the first of two papers, the details and results of a systematic, carefully standardized application of dye dilution technic to the measurement of cardiac output are reporte(l. A substantially reduced output was a consistent finding in older subjects. Fa(tors responsible for this are analyzed in this article, and further interpretations are made in the succeedinig a1rticle. One result of the analysis of time-concentration curves of dye provides an interesting relationship to (linical estimates of circulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
155
6
3

Year Published

1966
1966
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 530 publications
(185 citation statements)
references
References 20 publications
19
155
6
3
Order By: Relevance
“…Where cardiac output was decreased, the cerebral coronary and skeletal blood flow tended to be maintained at the expense of supply to other organs including the liver. Brandfonbrener, Landowne & Shock (1955) Sherlock et al (1950) estimated hepatic blood flow from the extraction of bromsulphthalein and concluded that it was reduced by 40-50% at the age of 60 when compared to that in individuals averaging 25 years. As the average age of elderly subjects was 78 years, the longer half-life after i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Where cardiac output was decreased, the cerebral coronary and skeletal blood flow tended to be maintained at the expense of supply to other organs including the liver. Brandfonbrener, Landowne & Shock (1955) Sherlock et al (1950) estimated hepatic blood flow from the extraction of bromsulphthalein and concluded that it was reduced by 40-50% at the age of 60 when compared to that in individuals averaging 25 years. As the average age of elderly subjects was 78 years, the longer half-life after i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies by the group of Dr. Nathan Shock in Baltimore strongly supported this thesis. In so-called healthy human volunteers, the cardiac output (Brandfonbrener et al 1955), renal creatinine clearance (Rowe et al 1976) and all other physiological parameters examined were demonstrated to steadily decline with age. However, later by the same group in Baltimore, in a longitudinal study, neither the cardiac output (Rodeheffer et al 1984) nor renal creatinine clearance (Lindeman et al 1985) was shown to decline with age.…”
Section: What Really Declines With Age?mentioning
confidence: 99%
“…Performance on reaction-time tests of attention and memory retrieval was slower for the older adults than for a comparison group of 24 young adults, and there was no improvement in the older adults' performance on these tests as a function of aerobic exercise training. Results suggest that exercise-related changes in older adults' cognitive performance are due either to extended periods of training or to cohort differences between physically active and sedentary individuals.Several parameters of cardiovascular functioning (e.g., maximal heart rate, cardiac output, and left ventricular ejection fraction during exercise) typically exhibit a decline during later adulthood, even in the absence of overt coronary disease (Brandfonbrener, Landowne, & Shock, 1955;Gerstenblith, Lakatta, & Weisfeldt, 1976;Port, Cobb, Coleman, & Jones, 1980;Strandell, 1976). There is, in addition, a significant agerelated decline in cardiorespiratory fitness (i.e., aerobic capacity), the ability to sustain maximal expenditures of energy.…”
mentioning
confidence: 99%